Characterising the axial phenotype of psoriatic arthritis: a study comparing axial psoriatic arthritis and ankylosing spondylitis with psoriasis from the REGISPONSER registry. Issue 2 (5th December 2022) - Michelena, Xabier; López-Medina, Clementina; Erra, Alba; Juanola, Xavier; Font-Ugalde, Pilar; Collantes, Eduardo; Marzo-Ortega, Helena
Abstract : Aims: To explore the clinical and radiographical characteristics of axial psoriatic arthritis (PsA) and to compare it with ankylosing spondylitis (AS) with psoriasis. Methods: Cross-sectional study from the national multicentre registry REGISPONSER where participants fulfilled the European Spondyloarthropathy Study Group spondyloarthritis criteria at entry. Clinical, laboratory and radiographical characteristics between patients classified as axial PsA and AS with psoriasis by their rheumatologist are compared according to HLA-B27 status. Results: Of 2367 patients on REGISPONSER, n=405 had PsA, of whom 27% (n=109) had axial involvement as per the treating rheumatologist. 30% (n=26/86) of axial PsA were HLA-B27 positive. In the AS group, 9% (127/1422) had a history of psoriasis and were more frequently male, with longer diagnostic delay and more anterior uveitis than those with axial PsA who had more peripheral involvement and nail disease. Patients with HLA-B27-negative axial PsA reported less inflammatory pain and structural damage compared with AS with psoriasis. By contrast, HLA-B27-positive axial PsA shared clinical characteristics similar to AS and psoriasis although with a lower BASRI score. In the multivariable analysis, patients with AS and psoriasis were independently associated with HLA-B27 positivity (OR 3.34, 95% CI 1.42 to 7.85) and lumbar structural damage scored by BASRI (OR 2.14, 95% CI 1.4 to 3.19). Conclusion: The more prevalent axial PsA phenotype is predominantly HLA-B27 negative and presents different clinical and radiological manifestations when compared with AS with psoriasis. There is great heterogeneity in what rheumatologists consider axial PsA from a clinical and imaging perspective, highlighting the need for research into possible genetic drivers and a consensus definition.